Réponses

  • Omnes
  • Modérateur confirmé
2014-03-07T16:04:06+01:00
Salut,
Exercice 1:

1) (3x+2)² - 5 = 9x² + 12x + 4 - 5 = 9x² + 12x - 1
2)
a) f(0) = -1
b) f(0) = 9*0² + 12*0 - 1 = -1

3)
a) Les antécédents de 0 par f sont : -1.4 et 0.1.
b)
 f(x) = (3x+2)² - 5
f(x) = (3x + 2)² -  \sqrt{5}^{2}
f(x) = (3x + 2 +  \sqrt{5} )(3x+2-  \sqrt{5} )

c)
 f(x) = 0
(3x + 2 +  \sqrt{5} )(3x+2-  \sqrt{5} ) = 0
(3x + 2 +  \sqrt{5} ) = 0
3x = -2 -  \sqrt{5} .

x =  \frac{-2- \sqrt{5} }{3}
(3x+2-  \sqrt{5} )  = 0
3x = -2 +  \sqrt{5}
x =  \frac{-2  +  \sqrt{5} }{3}

Exercice 2:

1)

J =  5 \sqrt{12} + 8 \sqrt{27} - 5  \sqrt{75}  = 5 \sqrt{4*3} + 8  \sqrt{9*3} - 5  \sqrt{25*3} \\
J = 5* \sqrt{4} *  \sqrt{3} +  8 \sqrt{9} *  \sqrt{3} - 5 \sqrt{25} *  \sqrt{3}   \\
J = 10\sqrt{3}+ 24\sqrt{3} - 25\sqrt{3}\\
J = 9\sqrt{3}

2)

K =  \frac{2*(10^{3})^{2}  }{5*10^{-4} } =  \frac{2*10^{3*2} }{5*10^{-4} } =  \frac{2*10^{6} }{5*10^{-4} }  =  \frac{2}{5} * 10^{6-(-4)} = \frac{2}{5} * 10^{10}

3)

 \frac{2}{3} -   \frac{\frac{5}{3} }{ \frac{8}{7} }  =  \frac{2}{3} - \frac{5}{3} * \frac{7}{8} =  \frac{2}{3} -  \frac{35}{24} =  \frac{16-35}{24}  =  \frac{-19}{24}

Bonne journée !